1985
DOI: 10.1073/pnas.82.22.7691
|View full text |Cite
|
Sign up to set email alerts
|

Natural effector T lymphocytes in normal mice.

Abstract: The "natural" T-cell activity in normal unimmunized mice was studied. By double-parameter fluorescence-activated cell sorter analysis, it was found that 5-10% of all splenic Lyt-2+ and L3T4+ lymphocytes are large, of which more than half are in mitotic cycle. In contrast with small resting cells of the same phenotype, activated (large) T cells isolated from normal mice are functional effector cells: L3T4+ large cells induce normal B lymphocytes into proliferation and antibody secretion, while large Lyt-2+ cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
51
1

Year Published

1986
1986
2003
2003

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(57 citation statements)
references
References 23 publications
5
51
1
Order By: Relevance
“…Selftolerance in normal individuals is likely to be, at least in part, achieved by similar mechanisms. Thus, normal and antigenfree mice contain high numbers of activated B and T cells (33,34). Importantly, CD8' blasts isolated from normal mice are efficient suppressors of B-cell response but lack cytotoxic ability, while helper cells but not inflammatory CD4' cells are naturally activated.…”
Section: Resultsmentioning
confidence: 99%
“…Selftolerance in normal individuals is likely to be, at least in part, achieved by similar mechanisms. Thus, normal and antigenfree mice contain high numbers of activated B and T cells (33,34). Importantly, CD8' blasts isolated from normal mice are efficient suppressors of B-cell response but lack cytotoxic ability, while helper cells but not inflammatory CD4' cells are naturally activated.…”
Section: Resultsmentioning
confidence: 99%
“…Thymocytes were fractionated over discontinuous Percoll gradients (Amersham Pharmacia Biotech) (28). Cells with densities of 1.060 Ͻ o Ͻ 1.070 and p Ͼ 1.070 were collected and classified into large (significantly enriched for medullary thymocytes) and small (cortical) thymocytes according to an established protocol (7).…”
Section: Preparation Of Human Medullarymentioning
confidence: 99%
“…In contrast, naturally activated CD8 + splenocytes showed suppressive activity, inhibiting the proliferation and Ig secretion of LPS-stimulated B cells [11]. Naturally activated T cells proliferated poorly in response to polyclonal stimuli such as Con A, anti-CD3 antibodies or PMA/ ionomycin, even in the presence of IL-2 [12].…”
Section: Introductionmentioning
confidence: 85%
“…We found that naturally activated CD4 + T cells are enriched for cells expressing activation markers and producing IL-4, IL-10 and IFN-+ . As demonstrated before [11], the large activated CD4 + T cells are effector helper T cells. We also found that a large proportion of IL-4-and IL-10-producing CD4 + T cells simultaneously produced IFN-+ .…”
Section: Introductionmentioning
confidence: 87%